Developing University Students’ Transferable Skills Through Object-Based and Collaborative Learning - Victoria Jackson (GiLE Journal of Skills Development)
This empirical paper reports on the findings of a pilot study that aimed to explore student attitudes towards the innovative use of the arts to develop university students’ transferable skills. Postgraduate business and management students were taken to a local museum and nearby art gallery to undertake a guided object-based learning activity. The art centre activities were designed to help students to learn, practice and develop key transferable skills through collaboration in an experiential learning setting. Methods: A questionnaire was dispersed to the students after the second trip had taken place, to ascertain student feedback on both their experience and skill development because of the object-based learning approach. Results: Of the 21 students who took part in the museum and art gallery trips, a total of 19 completed the questionnaire. The results show that the students found their visits to the museum and art gallery to be valuable, enjoyable, and social, while also gaining new skills. The quantitative and qualitative analysis supports that these experiences were especially effective in fostering discussions among students, promoting critical thinking through object-based learning, and allowing students to compare their perspectives with those of their peers. This study supports the use of informal learning environments like museums and galleries as they can be highly effective in complementing traditional classroom education by encouraging deeper engagement and support a shift toward more interactive, discussion-driven education. This deeper learning approach fosters critical thinking, cultural competence, and teamwork, thus simulates key skills employers seek in the workplace.